Late Summer Peak and Scavenging-Dominant Metal Fluxes in Particulate Export Near a Seamount in the Western North Pacific Subtropical Gyre - Yamaoka, Kyoko; Suzuki, Atsushi; Tanaka, Yuichiro; Suzumura, Masahiro; Tsukasaki, Ayumi; Shimamoto, Akifumi; Fukuhara, Tatsuo; Matsui, Takaaki; Kato, Shogo; Okamoto, Nobuyuki; Igarashi, Yoshiaki (Frontiers in Earth Science, 2020)
We measured sedimentation fluxes around JA06 Seamount (Xufu Guyot; 19°30′N, 158°00′E) as part of an environmental baseline survey in Japan’s exploration area for cobalt-rich crusts in the subtropical Northwest Pacific. Sinking particles were collected at the flat top (sediment trap depths: 900 and 1000 m) and northeastern base (sediment trap depths: 1000 and 4720 m) of the seamount from June 2016 to April 2017. Total mass fluxes were very low, with average values of 4.3–4.9 mg m–2 d–1 and 9.3 mg m–2 d–1 in the shallow traps at the flat top and base, respectively, which is consistent with an oligotrophic system. The lower fluxes at the flat top probably reflect lower productivity of siliceous microplankton, such as diatoms. However, we were unable to substantiate any potential mechanisms for this difference in productivity and cannot evaluate whether this is representative of typical conditions. When combined with previous observations at two adjacent seamounts, our results indicate widespread seasonality in sediment fluxes with a peak in late summer (August–September). However, satellite data indicate that summer is the season with the lowest primary production. This discrepancy could be explained either by phytoplankton blooms fueled by symbiotic nitrogen fixation that only cause minor increases in surface-ocean chlorophyll or short-lived blooms induced by passing typhoons under thick cloud cover. At the base site, we also analyzed material and element transport rates from shallow to deep waters. Half of the organic matter and >80% of the carbonate in sinking particles was not degraded in the water column, suggesting that most of the regeneration of these materials occurs near or on the sediment surface. Furthermore, four major processes appeared to control elemental fluxes in the area: lithogenic (Al, Ti, Fe), carbonate (Mg, Ca, Sr), biogenic (+scavenging) (Ni, Zn, Cd, Pb), and scavenging (V, Mn, Co, Cu, rare earth elements) processes. The estimation of excess flux based on the composition of upper continental crust demonstrated that >85% of total Mn, Co, Ni, Cu, Zn, Cd, and Pb fluxes were attributable to scavenging (+biogenic uptake). Scavenging-dominant metal fluxes are likely ubiquitous in the oligotrophic open ocean.